Early occurrence of acute myelomonocytic leukemia (M4/M5) after liver transplantation: a case report - Farhad Zamani; Hanie Karimi; Mohsenreza Mansoorian; Ali Basi; S. Ahmad Hosseini; Zahra Zahed; Nasim Seyedghasemipour; Roghayeh Sahraie (Journal of Medical Case Reports, 2023)
Abstract Introduction Acute myeloid leukemia is a rare event in post-liver-transplantation recipients. In the present report, we described a case of extramedullary acute myeloid leukemia, M4/M5 subtype, following orthotopic liver transplant. Case presentation The patient was a 50-year-old Iranian woman who underwent orthotopic liver transplant due to hepatitis B-related cirrhosis (Child C, MELD (model for end-stage liver disease score) = 22). Orthotopic liver transplant was performed using the piggy back technique in January 2022. Induction immunosuppressive therapy was 1 gm methylprednisolone for 3 days followed by a triple maintenance immunosuppressive regimen including mycophenolate mofetil, prednisolone, and tacrolimus. About 5 months after orthotopic liver transplant in June 2022, the patient presented with leukocytosis, with white blood cell count of 99.4 × 103/µl, and physical examination revealed only cervical lymphadenopathy. Biopsy of cervical lymph nodes showed a myeloid tumor. She was immediately hospitalized. Eight hours after hospitalization, the patient gradually developed lethargy and decreased O2 saturation to approximately 89%. Flow cytometry demonstrated the markers of a myelomonocytic acute myeloid leukemia (M4/M5). Cytoreduction was immediately started by intensive leukopheresis followed by induction therapy. Because of a septic complication during the induction therapy, further chemotherapy was discontinued and broad-spectrum antibiotics and antifungal treatments started. Unfortunately, our patient died of severe septic shock 42 days after hospitalization. Conclusion Acute myeloid leukemia is a rare phenomenon after liver transplantation, and it can follow a rapidly fatal clinical course.